Wiedeński okres w życiu Adolfa Hitlera w ujęciu Brigitte Hamann i Augusta Kubizka - Maciejewski, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article discusses the literature and the findings concerning the relatively least explored questions concerning Adolf Hitler, namely those of his youth. As the author stresses, just over a decade ago Polish readers interested in the Hitler phenomenon knew much less than they do now. Thanks to several books recently published in Poland they have had a chance to considerably expand their knowledge. The present author points to two figures, Brigitte Hamann and August Kubizek, focusing on the similarities and differences in their approach to this period of Hitler’s life.
Keywords: Hamann, Brigitte; Hitler, Adolf; Kubizek, August; Vienna